Exploring students’ spatial reasoning ability in solving geometry problems based on the learning style - Fadhilah, Maiputri Nur; Masduki (AIP conference proceedings, 2023)
This study aims to describe students’ spatial reasoning abilities in solving geometry problems based on the learning styles. The subjects in this study were 12th-grade students in one of the private schools in North Klaten, each of which had visual, auditory, and kinesthetic learning styles. Data collection techniques used were questionnaires, tests, interviews, and documentation. The data validity technique employed in this research was the triangulation method. Data analysis techniques utilized were data reduction, data presentation, and conclusions drawing. The results showed that the student with visual learning style was able to master indicators of spatial visualization, mental rotation, and spatial orientation, the student with auditory learning style was able to master indicators of spatial visualization, and the student with kinesthetic learning style was able to master spatial orientation indicators.